Paradigma Pendidikan Seni melalui Ideologi Liberal dan Ideologi Konservatif dalam Pembelajaran Sebagai Wujud Penguatan Karakter Individu - Arqam, Muh.; Budi Zakia Sani, Muhammad; Wijaya, Barkah Bangkit; Sastrabayu, Akhmad Mu'izzanur (GETER : Jurnal Seni Drama, Tari dan Musik, 2025)
The purpose of this article is to provide an art education perspective through liberal and conservative ideologies in an art education review. The method in this paper applies a qualitative descriptive type with a conceptual approach. Content analysis is carried out from articles, books, and expert opinions. This conceptual article was analyzed sharply to obtain conclusions. The results of the analysis show that art education leads to two things, namely as a media for artistic expressive education and as an aesthetic appreciative. Thus, learning through art education functions as an agent of renewal that acts as a communicator and functions as a service based on taste, professionalism and always has an awareness of responsibility and functions as a trusted resource person